Analysis of Students' Mathematical Critical Thinking Skills Reviewed from Gender in SPLDV Material - Yulia Tiara Tanjung; Muhammad Razali (OMEGA: Jurnal Keilmuan Pendidikan Matematika, 2025)
Mathematics as a science that underlies the development of technology and plays an important role in the development and encourages the progress of other sciences. Students' ability to think to solve problems is certainly different, as is the case between male and female students. Gender differences are a term that emphasizes males and females. This type of research is a descriptive type of research with a qualitative approach that aims to describe Mathematical Critical Thinking Skills Reviewed from a Gender Perspective on SPLDV Material. This research was conducted at SMP IT Daarul Istiqlal located on Jl. Pantai Rambung in the 2024/2025 academic year. The subjects in this study were class VIII-2. The technique for taking research subjects was 20 male and 20 female people. Data analysis techniques were carried out with steps of data validity, data reduction, data presentation, and verification and conclusions. Indicators of mathematical critical thinking skills in this study are: (1) Finding ways that can be used to deal with problems, (2) Analyzing Data, (3) Evaluating relevant arguments in solving a problem.